2020
DOI: 10.21203/rs.3.rs-16613/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between learning environment variables and students’ approaches to studying: a cross-sectional study

Abstract: Background: Aspects of the learning environment may be related to students` approaches to studying, but few studies have investigated these relationships in the context of occupational therapy education.Objective: To examine associations between occupational therapy students’ perceptions of the learning environment and their approaches to studying.Method: 187 first-year occupational therapy students in Norway (response rate 61.3 %) participated in this study. Aside from sociodemographic information, the studen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Sometimes the fear of failure due to heavy workloads or a huge amount of study material may lead to a decline in motivation and push the students towards a surface approach study behavior. 16 As a result of this research, it was shown that medical and dentistry students have different learning approaches, and medical students are favored deep and strategic learning approaches. Using data from a single private institution, selecting only two faculties, and evaluating first-year students were all limitations.…”
Section: Discussionmentioning
confidence: 85%
“…Sometimes the fear of failure due to heavy workloads or a huge amount of study material may lead to a decline in motivation and push the students towards a surface approach study behavior. 16 As a result of this research, it was shown that medical and dentistry students have different learning approaches, and medical students are favored deep and strategic learning approaches. Using data from a single private institution, selecting only two faculties, and evaluating first-year students were all limitations.…”
Section: Discussionmentioning
confidence: 85%
“…9 Mork e colaboradores também identificaram que a sobrecarga de estudos reduz a motivação e instiga o medo do fracasso, levando a comportamentos de estudo de AS. 20 Nesses dois trabalhos, a utilização de estratégias AP também foi atribuída a uma menor disponibilidade de tempo para os estudos.…”
Section: Discussionunclassified
“…The study is a sub‐study of a larger study of occupational therapy students. The research project as a whole is a longitudinal study of study approaches (Gramstad et al, 2020; Mørk et al, 2020) and the perceived learning environment (Bonsaksen et al, 2019; Bonsaksen, Gramstad, Mørk, & Johnson, 2019; Thordardottir et al, 2020; Thygesen et al, 2020) among undergraduate occupational therapy students in Norway. One student cohort was followed‐up with one annual survey in each of their 3 study years.…”
Section: Methodsmentioning
confidence: 99%